Efficient Self-Assembly of mPEG End-Capped Porous Silica as a Redox-Sensitive Nanocarrier for Controlled Doxorubicin Delivery - Anh Khoa Nguyen; Thi Hiep Nguyen; Bui Quoc Bao; Long Giang Bach; Dai Hai Nguyen (International Journal of Biomaterials)
Porous nanosilica (PNS) has been regarded as a promising candidate for controlled delivery of anticancer drugs. Unmodified PNS-based nanocarriers, however, showed a burst release of encapsulated drugs, which may limit their clinical uses. In this report, PNS was surface conjugated with adamantylamine (ADA) via disulfide bridges (-SS-), PNS-SS-ADA, which was further modified with cyclodextrin-poly(ethylene glycol) methyl ether conjugate (CD-mPEG) to form a core@shell structure PNS-SS-ADA@CD-mPEG for redox triggered delivery of doxorubicin (DOX), DOX/PNS-SS-ADA@CD-mPEG. The prepared PNS-SS-ADA@CD-mPEG nanoparticles were spherical in shape with an average diameter of 55.5 ± 3.05 nm, a little larger than their parentally PNS nanocarriers, at 49.6 ± 2.56 nm. In addition, these nanoparticles possessed high drug loading capacity, at 79.2 ± 3.2%, for controlled release. The release of DOX from DOX/PNS-SS-ADA@CD-mPEG nanoparticles was controlled and prolonged up to 120 h in PBS medium (pH 7.4), compared to less than 40 h under reducing condition of 5 mM DTT. Notably, the PNS-SS-ADA@CD-mPEG was a biocompatible nanocarrier, and the toxicity of DOX was dramatically reduced after loading drugs into the porous core. This redox-sensitive PNS-SS-ADA@CD-mPEG nanoparticle could be considered a potential candidate with high drug loading capacity and a lower risk of systemic toxicity.